Merging Virtual World with Real-Life Behavior: A Concept for a Smartphone App to Influence Young People's Travel Behavior. Issue 4 (April 2019) - Roider, Oliver; Wegener, Sandra; Stark, Juliane; Judmaier, Peter; Michelberger, Frank; Barberi, Alessandro
European trends in children's travel patterns show decreasing rates of trips walked or cycled. Against this background, a concept for a smartphone app was developed to promote active travel modes for children and adolescents. The app collects players' travel data as input for a game: a high level of real-life environmentally friendly and active travel modes leads to a higher score. Competing players redeem the points they have collected to reach specific virtual locations on a map and win real-life rewards (e.g., shopping vouchers). The game was developed based on the user-centered design approach—an iterative process between design, prototyping, and evaluation. This paper presents the game concept alongside the results of a prototype field test at three schools in the province of Lower Austria, comprising 57 students aged 12 to 18. Results suggest that the game was easy to use and entertaining. However, younger players lost interest faster than older ones. Players emphasized improvements in relation to mode detection and tracking of individual trips, since fair playing conditions were requested by all age groups. Although the level of knowledge about sustainable mobility is high among young people, the game was rated as being a good tool for raising awareness regarding the environmental and health effects of mode choice. The promising results of this research project need to be transferred into a business model that can provide ongoing game updates, keep the players interested, and achieve long-term effects.